Assessing the incidence and wage effects of overeducation among Italian graduates using a new measure for educational requirements - Luca Cattani; Giovanni Guidetti; Giulio Pedrini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2014)
This paper investigates three dimensions of overeducation: incidence, impact on earnings and possible determinants. The analysis focuses on Italian graduates and refers to the cohort that graduated in 2007 using data from the AlmaLaurea survey on graduates' career paths. A new measure of overeducation is introduced and it is jointly examined along with other pre-existing measures based on workers' self-assessment. The analysis is carried out by comparing the different results obtained adopting the two different measures of overeducation. Results show that the newly introduced measure can deal with the biases affecting workers' self- assessment measures.
Keywords: I2; J31; 330